PERSPEKTIF PENGEMBANGAN INDUSTRI GULA DI INDONESIA - INDRANINGSIH, KURNIA SUCI; MALIAN, A. HUSNI (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 6, No. 1 Februari 2006)
Sugar cane planted-area in Java is limited and supply of raw material for sugar companies (PG) is possible through improvement of sugar cane productivity and sugar content. It is necessary to implement individual sugar content or minimal sugar content guarantee between farmers’ group and PG’s management. PG expansion to uotside Java (Sumatera, Sulawesi, Maluku and Papua) is urgent, at least 15 new PG, in order to lessen dependence on sugar production from Java Island. PG located outside Java are designed not to produce sugar only, but also to make derivative products such as ethanol, alcohol, etc. Revitalizing research and development activities is necessary to generate new technology.
Keywords: Perspective, Development, Sugar Industry